Electrical properties of the sensory neuron and defense reactions of mollusc Lymnaea stagnalis at conditions of prolonged hyperglycemia - Sidorov, Alexander V.; Shadenko, Viktoria N. (Experimental Biology and Biotechnology, 2022)
Hemolymph glucose level rise (from 0.12 (0.05; 0.18) to 4.10 (3.18; 6.08) mmol/L) modify the defensive behaviour of molluscs. This results in increase of the degree of animal’s body retracted into the shell and in reinforcement of weak defense reactions in response to tentacles’ tactile stimulation. No fluctuations in the tentacles length and the duration of the latent period of protraction were found. At experimental hyperglycemia (incubation of the isolated CNS preparation in 10 mmol/L D-glucose solution for 2 h), the basic electrical characteristics of FMRFamide-containing neuron RPaD1, involved in sensory stimuli detection and heart beat regulation in Lymnaea, were changed. Membrane depolarisation, accompanied by firing rate increase were observed, while current-voltage curve characteristics, as well as membrane resistance, capacity and time constant remains unchanged in comparison with control. An increase in rising and falling phases duration, undershoot amplitude were noted, while other parameters of the RPaD1 spike remained unchanged. Based on the revealed features of the action potential shape at hyperglycemia, it is assumed that these changes can be caused by the activation of the Na+-glucose co-transporter and ATP-sensitive K+-channels of the RPaD1 membrane. The action of glucose should be considered as a metabolic signal also in relation to non-feeding neurons in the mollusc brain.